Long Non-Coding RNAs in the Tumor Immune Microenvironment: Biological Properties and Therapeutic Potential - Pi, Ya-Nan; Qi, Wen-Cai; Xia, Bai-Rong; Lou, Ge; Jin, Wei-Lin (Frontiers in Immunology, 2021)
Cancer immunotherapy (CIT) is considered a revolutionary advance in the fight against cancer. The complexity of the immune microenvironment determines the success or failure of CIT. Long non-coding RNA (lncRNA) is an extremely versatile molecule that can interact with RNA, DNA, or proteins to promote or inhibit the expression of protein-coding genes. LncRNAs are expressed in many different types of immune cells and regulate both innate and adaptive immunity. Recent studies have shown that the discovery of lncRNAs provides a novel perspective for studying the regulation of the tumor immune microenvironment (TIME). Tumor cells and the associated microenvironment can change to escape recognition and elimination by the immune system. LncRNA induces the formation of an immunosuppressive microenvironment through related pathways, thereby controlling the escape of tumors from immune surveillance and promoting the development of metastasis and drug resistance. Using lncRNA as a therapeutic target provides a strategy for studying and improving the efficacy of immunotherapy.